Preparation and characterization of novel UV-curable ester methacrylate crosslinking-agents and their structure-property relationships, 2 - (:unkn) unknown (WILEY-V C H VERLAG GMBH, 2001)
Full Paper: Four, new difunctional monomers namely 2,2-bis(4-ethoxyacrylatephenyl)propane (HEPAAC), 2,2-bis(4-ethoxyacrylatephenyl) 6Fpropane (HEPFAAC), 2,2-bis (4-ethoxyacrylate-3,5-dibromophenyl)propane (TBHEPAAC) and 5-tert-butyl-1,3-bis(4-ethoxyacrylate benzoyl)benzene (tBuHEPBAC) containing acrylic moiety, which can be good candidates as x-linking agents for UV curable coating applications, were synthesized by reacting acryloyl chloride with four different diols. The structures of the monomers thus prepared were characterized by FTIR, mass and H-1 NMR spectroscopies. Introduction of 10% of these new monomers into the UV-curable formulations, caused different behaviors in tensile strengths and elongations, when compared with diethylene glycol di-acrylate (DEGDA) containing films. Both elongation and tensile strength values were decreased for TBHEPAAC and tBuHEPBAC containing-films, while-the same values of the films containing HEPAAC and HEPFAAC's increased. Gel contents of the UV-cured:polymeric films were found: id be: between 88-98%. Thermogravimetric; analysis showed that there were not appreciable changes in thermal stability of the films compared to DEGDA containing ones. On the other hand, HEPFAAC and tBuHEPBAC containing films showed increases in char yields due to the presence of F and Br in their structures. Introduction of the new difunctional monomers lowered the water absorption values of the films somewhat proportional to the methyl group content of the x-linkers.